A carga dos transtornos mentais e do suicídio no estudo de Carga Global de Doença no Brasil - Cecília Silva Costa Bonadiman (2020)
Introduction: Mental and substance use disorders (MD), especially depressive disorders, are among the leading causes of non-fatal disease burden worldwide and are associated to mortality for suicide. The present study aimed to describe and analyze the Global Burden of Disease Study (GBD) estimates for MD and suicide in Brazil and Federated Units (FUs) and was prepared in the form of three scientific articles. The objective of the first article was to describe the data related to the burden of MD, in GBD-2015, in Brazil and its FUs, by age and sex, in the years 1990 and 2015. The second article used GBD-2017 study methodology to evaluate the prevalence estimates, the disability-adjusted life years (DALY) and the years lived with disability (YLD) for depressive disorders in Brazil and FUs, by sex and age, in 1990 and 2017. The YLD estimates were compared to those of seven other countries. The observed versus expected YLD, based on the sociodemographic index (SDI), were compared. Finally, the third article use the estimates from the GBD-2017 to describe mortality and years of life lost (YLL) by suicide in Brazil and FUs by sex and age groups, in 1990 and 2017. Methods: A descriptive study was carried out with secondary data from GBD study. In GBD studies, burden of disease is measured in terms of DALY, a composite indicator that results from the sum of YLD and YLL: DALY=YLD+YLL. The calculation of YLDs was performed by multiplying two components: the prevalence of depressive disorders and the disability weight. To estimate the YLL, the source of mortality data in Brazil is the Mortality Information System (Sistema de Informação sobre Mortalidade [SIM]). The GBD uses methodologies for correcting underreporting of deaths and garbage code. Age-standardised rates per 100 thousand inhabitants produced by the direct standardization method, with the world population developed for GBD. For all estimates, uncertainty intervals of 95% (95% UI) were considered. Results: Article 1. In Brazil, despite low mortality rates, there has been a high burden for mental and substance use disorders since 1990, with high YLD. In 2015, these disorders accounted for 9.5% of all DALY in Brazil, ranking in the third and first position in DALY and YLD, respectively, with an emphasis on depressive and anxiety disorders. Drug use disorders had their highest increase in DALY rates between 1990 and 2015 (37.1%). The highest proportion of DALY occurred in adulthood and in females. There were no substantial differences in burden of mental and substance use disorders among FUs. Article 2. In GBD-2017, the prevalence of depressive disorders in Brazil was 3.30% (95% UI: 3.08 to 3.57), ranging from 3.79% (3.53 to 4.09) in Santa Catarina to 2.78% in Pará (2.56 to 3.03), with significant differences between the FUs. From 1990 to 2017, there was an increase in number (55.19%, 49.57 to 60.73) and crude rate of YLD (9.48%, 5.51 to 13.38), but a decrease in the age-standardized rates (-9.01%, -11.66 to - 6.31). The highest proportion of YLD was observed in the age range of 15-64 years and among females. These disorders rank 4th and 13th as leading causes of YLD and DALY, respectively, in Brazil. In the other countries evaluated, the ranking of these disorders in the YLD classification was close to Brazil´s, while in the DALY classification, there was higher variability. All countries had YLD rates similar to the overall rate. The observed/expected YLD ratio ranged from 0.81 in Pará to 1.16 in Santa Catarina. Morbidity of depressive disorders was not associated with SDI. Article 3. There were 14 145 (95% UI: 13 373 to 14 566) suicide deaths in Brazil in 2017, an increase of 53.21% (43.24 to 59.40%) compared to 1990. The crude mortality and YLL rates increased by 8.08 % (1.05 to 12.44%) and 0.38% (-6.45 a 4.91) respectively, while there was a decrease in age-standardised rates of mortality (-15.00%, -20.33 to -11.98%) and YLL (-11.88%, -17.70 to -8.28%). In 2017, the highest age-standardised mortality rates were found in southern FUs, but from 1990 to 2017, there was a decrease in rates in all Southern and Southeastern FUs and an increase in almost all Northeastern UFs. In both sexes, about two-thirds of the number of suicides occurred between 15 and 49 years of age, while the highest rates occurred at more advanced ages, for ages 75 years or older. Men were at least three times more affected than women in all FUs and age groups, except for ages 10-14 years when the numbers were similar. Only for those aged 10-14 years there was an increase in the suicide rate between 1990 and 2017. Suicide was the 3rd leading cause of death in men aged 15-34 years and the 4th in women aged 15-24 years. Conclusions: Mental and substance use disorders, especially depressive disorders, are highly disabling. Depressive disorders and suicide are increasing every year, indicating the need for preventive and protective actions, at all levels of attention to these cases. The elucidation of epidemiological aspects of mental and substance use disorders and suicide in all Brazilian states is crucial for planning action aimed at the areas of greast need and to making the Brazilian health system more equitable. Furthermore, it provides data to expand the discussion about distribution and aspects related in each locality, which still are scarce in the country.